2020
DOI: 10.1002/pc.25693
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal gradient on interfacial behavior of hybrid fiber reinforced polypropylene composites fabricated by injection overmolding technique

Abstract: Hybrid fiber reinforced thermoplastic composites, fabricated by overmolding technique, are a novel class of lightweight components that benefit from the high mechanical performance of continuous fiber reinforced thermoplastics (CFRT) as well as geometric complexity because of short fiber reinforced thermoplastics (SFRT) composites architecture. The heterogonous interface between CFRT and SFRT in the hybrid structure was generated when SFRT was injected on CFRT surface during overmolding processing. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Sketch map of the special fixture and test sample are shown in Figure 2, as reported in our previous study. 36 Five samples were repeated for each group. The calculation formula of interfacial shear strength τ is as follows:…”
Section: Single-lap-shear Testsmentioning
confidence: 99%
“…Sketch map of the special fixture and test sample are shown in Figure 2, as reported in our previous study. 36 Five samples were repeated for each group. The calculation formula of interfacial shear strength τ is as follows:…”
Section: Single-lap-shear Testsmentioning
confidence: 99%
“…However, the resin temperature was lower than the cylinder temperature by approximately 10°C. The interface temperature (𝑇𝑇 𝑖𝑖 ) is predicted by the following equation [17]:…”
Section: Influence Of Molding Conditions and Cnf Content On The Joini...mentioning
confidence: 99%
“…The welding mechanisms are described by (i) intimate contact development by providing the pressure and (ii) interdiffusion of polymer chains across the interface by heat transfer [9]. Furthermore, the crystalline structure of semicrystalline polymers, such as polypropylene (PP), polyamide (PA) and polyether ether ketone (PEEK), strongly depends on the temperature-related processing parameters during conventional injection molding [10]. Thus, the joining strength of the overmolded hybrid composite parts is controlled by the crystalline state and molding conditions.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most effective approaches is to reduce the vehicle weight. [1][2][3] It is reported that every 10% of the weight decrease in a vehicle would reduce 7% of fuel consumptions. 2 Multi-material structure design by joining different light materials (e.g., fiber reinforced polymer composites and metals) provides a great lightweight potential for automotive area, which combines the individual advantages of these materials into a hybrid structure with structural performance that is not present in either of two constituent materials independently.…”
Section: Introductionmentioning
confidence: 99%